Análisis de los factores económicos más influyentes en la exportación de textiles hacia Estados Unidos (2021)
This degree work is an investigation of the economic factors that influence the development, production and export of textile industry products to the United States. This document contains theoretical information about the manufacturing processes of the products, as well as the behavior of the textile market in recent years in both Colombia and the United States.